Transformation rate of nitrogen and sulphur compounds under changing anaerobic/anoxic conditions / Nurul Khamsatul Akma Kamalruzaman - Kamalruzaman, Nurul Khamsatul Akma (2008)
Microbial transformations in sewer networks involving mass transfer occur simultaneously within and across the different phases of the sewer environment namely the bulk water phase, the sewer submerged biofilm , the sewer sediments, the sewer atmosphere and sewer wall. These transformation occur either under aerobic, anaerobic or anoxic conditions depending on the types of electron acceptor available in wastewater. At present, transformation of sulphur compounds in wastewater has become a serious problem in sewer systems. Anaerobic conditions in sewer systems normally result in sulphide formation. Several methods have been investigated in order to control the formation of sulphide. Many studies have reported on addition of nitrate as the inhibitor in the sulphate reduction process. Much of these studies have focused on wastewater in temperate countries. However, information on the transformation rate of sulphur compounds in the wastewater is lacking for hot climate countries. Consequently, this study investigates the microbial transformation in sewer networks for hot climate countries under sewer conditions. Series of experiments were conducted to determine the transformation rates of sulphur and nitrogen compounds in municipal wastewater under changing anaerobic/anoxic/anaerobic condition and to establish the pathways for anoxic sulphur oxidation in municipal wastewater under sewer condition. The transformation rates of sulphate under anaerobic/anoxic/anaerobic conditions were found to be 0.127 mg S/(L h), 0.091 mg S/(L h) and 0.012 mg S/(L h) respectively while the utilization rate of nitrate under anaerobic/anoxic/anaerobic conditions are 0.014 mg N/(L h) ,1.185 mg N/(L h) and 0.003 mg N/(L h) respectively. A single step of sulphur oxidation process occurred during the anoxic condition. The lower oxidation state of sulphur compounds was oxidized directly to sulphate.